Desarrollo de una estrategia para la restauración ecológica con especies nativas en el área disturbada de la Estación Biológica Kutukú. - Angulo Naranjo, Sebastián Fernando (2018)
The present study was conducted in the disturbed area within the Kutukú Biological Station (EBK), located in the parish of Sevilla Don Bosco, Morona Santiago province; with the purpose of investigating the plant community and developing an ecological restoration strategy with native species. For this purpose, it was required to diagnose the floristic composition of the local species, the state of natural regeneration and the level of natural succession in which the ecosystem is located. Considering that the EBK, belongs to the Cordillera del Kutukú, was proceeded to divide the study area into three altitudinal floors, located at 900, 1100 and 1280 MASL, in which three sampling scenarios were drawn for this investigation. Denominated like: areas that present regeneration, wooded zones and existing clear ones. According to data obtained in the field, it was recorded that at the level of 900 MASL there were 20 native species that are promoting natural regeneration, at 1 100 MASL 32 species were found and at 1 280 MASL there were 29 species. In addition, as a result of sizing the sampled area, it was obtained that the proposed surface to be restored corresponds to 6.64 ha. As a final product of the research, an ecological restoration strategy was developed to enhance the natural regeneration of the ecosystem, through enrichment (scattered planting method) and a compact plantation, in both cases using 10 native species, among which are predominant: Heliocarpus americanus, Alchornea glandulosa Poepp., Cecropia cf. ficifolia. Keywords: Restoration strategy, ecological restoration, enrichment, natural regeneration, native species.